Thermo-Mechanical Fatigue (TMF) Model for (2017-T4) Aluminum Alloy under Variable Temperature - Al-Alkawi, Hussain J.; Fenjan, Raad M.; Abdul-Zahraa, Samar K. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this work, constant and increasing temperature fatigue interaction effect on fatigue behavior of 2017-T4 aluminum alloy was investigated. Fatigue tests at constant load constant temperature and constant load increasing temperature were performed for five applied stresses which are (350,275,200,175 and 150 MPa) that based on the tensile test behavior .The constant temperatures were room temperature (RT) (25 ?C) and 100 ?C. While the increasing temperatures were RT, 50 ?C, 100 ?C and 150 ?C for one test program. The constant fatigue property of the increasing temperatures was observed the worst case compared to the others constant fatigue properties. A new variable temperature fatigue damage model was proposed. It is based on the S-N curve and taking into account the effects of constant loads and variable temperature. A comparison between prediction of the proposed model and crack growth rate due to Miner rule was made. The results proved that this model is satisfactory and gave safe results than Miner rule compared to experimental data.